Cobalt Complexes: Introduction and Spectra Analysis - Sotiles, Anne Raquel; Massarotti, Fernando; Pires, Juliana Cristina de Oliveira; Ciceri, Maria Eugênia Facchin; Parabocz, Cristiane Regina Budziak (Orbital: The Electronic Journal of Chemistry, 2019)
Little abundant on the Earth's surface, cobalt is obtained from the extraction of ores and the most common oxidation states for this element are +2 and +3. The objective of this work was to obtain the hexamincobalt (III) chloride complex from binder substitution reactions and oxidation of the metal center. The complex was characterized by UV-Vis spectroscopy and FTIR. The characteristic bands of strain and stretching of the NH3 molecule present in the compound were identified by FTIR. In the UV-Vis, two bands referring to the electronic transitions 1A1g → 1T1g and 1A1g →1T2g were identified, in addition to the TCML load transfer band. This work aims to contribute to the practical classes of inorganic chemistry.DOI: http://dx.doi.org/10.17807/orbital.v11i6.1242